Epigenetics and type II diabetes mellitus: underlying mechanisms of prenatal predisposition - Sterns, J. David; Smith, Colin B.; Steele, John R.; Stevenson, Kimberly L.; Gallicano, G. Ian (Frontiers in Cell and Developmental Biology, 2014)
Type II diabetes mellitus (T2DM) is a widespread metabolic disorder characterized by insulin resistance resulting in abnormally high blood glucose levels. While the onset of T2DM is known to be influenced by a number of genetic factors, emerging research has demonstrated the additional role of a variety of epigenetic mechanisms in the development of this disorder. Epigenetics relates to the heritable changes in gene expression that cannot be explained by simple variations in the primary DNA sequence and includes DNA methylation and histone modification. These changes impact many processes, including stem cell differentiation into pancreatic endocrine cells as well as normal β-cell function. Recent studies focusing on the effects of maternal health, specifically as it is affected by famine and hyperglycemia, have found possible mechanisms to explain the increased likelihood of the fetus developing risk factors such as altered atherogenic lipid profiles, increased obesity and BMI, as well as impaired glucose tolerance (IGT) for the development of T2DM later in life. It is suggested that these epigenetic influences happen early during gestation and are less susceptible to the effects of postnatal environmental modification as was previously thought. Regardless, emerging research into epigenetic-based treatment approaches for T2DM are promising and offer yet another means by which to limit the impact of this global epidemic.